Gambaran Pemberian Layanan Kesehatan Di Panti Wredha Salatiga - Marsela Sahertian; Theresia Pratiwi Elingsetyo Sanubari; Kristiani Desimina Tauho (Jurnal Keperawatan Muhammadiyah, 2021)
A person in the elderly phase will experience a continuous aging process which is characterized by decreased physical endurance so that he is susceptible to disease and can cause death. One of the programs carried out to overcome these problems is health services in Panti Wredha. This health service is very important because it is able to realize a healthy, happy and productive old age for the elderly. However, there are still elderly people in Panti Wredha who do not receive assistance in health services due to the lack of health workers in the home for the elderly where they live. The purpose of this study was to determine the description of the provision of health services to the elderly at Panti Wredha Salatiga. This research uses descriptive qualitative method. Respondents in this study amounted to 13 participants consisting of doctors, nurses, cooks, the person in charge of data collection for the elderly in the elderly at home for the elderly and health workers who handle the elderly program in Salatiga City. Data analysis techniques were carried out by making interview transcripts, coding, determining themes and writing conclusions. This research was conducted during January-March 2020. The results of this study found that elderly health services in Salatiga City were not optimal. The provision of health services for the elderly at the Panti Wredha Salatiga is still dominated by the work of the nursing home independently. The health of ice, which functions as a health service provider, has not yet participated in this role. The health office focuses on implementing health service programs at the puskesmas because there is no cross-sectoral collaboration between the Panti Wredha in Salatiga City and the Salatiga City Health Office. So it is necessary to hope for cross-sectoral collaboration between the government and the private sector so that elderly health services in Salatiga City are mutually fulfilled.